TP53 mutation and survival in aggressive B cell lymphoma - Zenz, Thorsten; Hüllein, Jennifer (International journal of cancer, 2017)
TP53 is mutated in 20-25% of aggressive B-cell lymphoma (B-NHL). To date, no studies have addressed the impact of TP53 mutations in prospective clinical trial cohorts. To evaluate the impact of TP53 mutation to current risk models in aggressive B-NHL, we investigated TP53 gene mutations within the RICOVER-60 trial. Of 1,222 elderly patients (aged 61-80 years) enrolled in the study and randomized to six or eight cycles of CHOP-14 with or without Rituximab (NCT00052936), 265 patients were analyzed for TP53 mutations. TP53 mutations were demonstrated in 63 of 265 patients (23.8%). TP53 mutation was associated with higher LDH (65% vs. 37%; p < 0.001), higher international prognostic index-Scores (IPI 4/5 27% vs. 12%; p = 0.025) and B-symptoms (41% vs. 24%; p = 0.011). Patients with TP53 mutation were less likely to obtain a complete remission CR/CRu (CR unconfirmed) 61.9% (mut) vs. 79.7% (wt) (p = 0.007). TP53 mutations were associated with decreased event-free (EFS), progression-free (PFS) and overall survival (OS) (median observation time of 40.2 months): the 3 year EFS, PFS and OS were 42% (vs. 60%; p = 0.012), 42% (vs. 67.5%; p < 0.001) and 50% (vs. 76%; p < 0.001) for the TP53 mutation group. In a Cox proportional hazard analysis adjusting for IPI-factors and treatment arms, TP53 mutation was shown to be an independent predictor of EFS (HR 1.5), PFS (HR 2.0) and OS (HR 2.3; p < 0.001). TP53 mutations are independent predictors of survival in untreated patients with aggressive CD20+ lymphoma. TP53 mutations should be considered for risk models in DLBCL and strategies to improve outcome for patients with mutant TP53 must be developed.
Gesehen am 26.07.2018